(untitled) (International Journal of Environmental Sciences, 2025)
This action research explores the effects of hybrid distance instruction on learner engagement and speaking confidence in a university English course in Taiwan. The course combined face-to-face sessions, synchronous online classes via Microsoft Teams, and asynchronous activities on TronClass, enhanced by interactive tools such as ORID reflections, Padlet discussions, and group presentations. Data from student surveys (N = 30) and classroom observations reveal high satisfaction levels, with mean scores between 4.2 and 4.5 out of 5 across course design, video clarity, flexibility, and participation. Asynchronous components notably benefited introverted or anxious learners by providing a low-pressure environment for speaking practice. While students praised the course’s flexibility and clear materials, technical issues and time management challenges were reported. Findings suggest that carefully designed hybrid instruction can effectively promote engagement and oral confidence in higher education EFL contexts. Recommendations include scaffolding asynchronous speaking tasks, delivering timely feedback, and balancing synchronous and asynchronous elements to sustain learner motivation.